Failure characteristics of overlying strata and mechanism of strong ground pressure during the large‐scale and continuous mining of deep multi working faces - Defei Zhang; Yanan Gao; Guangkai Zhang; Zhenwei Tang; Feng Ding; Mingzhong Gao (Energy Science & Engineering)
Abstract In this study, a three‐dimensional large‐scale numerical model is established to investigate the failure characteristics of overlying strata and mechanism of strong ground pressure induced by excavation disturbance from multiple working faces. The characteristics of overlying strata fractures, heights of the caving zone and the fracture zone, and evolution of the stress field are systematically analyzed. The numerical simulation results reveal that the height of the caving zone after mining is 8.1 m, and that of the fracture zone is 27.3 m under the conditions of gently inclined thin coal seams. These findings are consistent with the theoretical results. The fracture development process can be divided into three stages: extensive development of new fractures, partial compaction of fractures, and closure of numerous fractures. In the structure of the post‐mining overlying rock, four stress zones are identified as follows: two zones of stress concentration at both ends of the working face, respectively, a zone of relatively high stress at the middle of the working face with low overlying strata, and a zone of stress fully released at the middle of the working face with high overlying strata. Comprehensive analysis of the maximum vertical stress of the cross section and the stress of the working face indicates that the stress increases significantly when mining enters the gob square stage and the roof does not collapse timely.